AB0254 Dynamics of Disease Activity Scores During the First 12 Weeks Allow to Predict the Necessity in Combination Therapy with Methotrexate and Biologics Within T2T Strategy in Patients with Early and Established Rheumatoid Arthritis (Remarca Study). (9th June 2015) - Karateev, D.; Luchikhina, E.; Demidova, N.; Loukina, G.; Kanonirova, M.; Olyunin, Y.; Aleksandrova, E.; Novikov, A.; Nasonov, E.
Abstract : Background: The Treat to Target (T2T) strategy in rheumatoid arthritis (RA) implies regular review of therapy in order to achieve the optimal outcome - remission or low disease activity (LDA). The majority of patients would require upgrade of therapy to drug combinations, including biologics. Prediction of the necessity of such upgrades is an important task for practitioners. Objectives: To identify factors, indicating the necessity of biologics in RA patients, treated in compliance with T2T strategy. Methods: The REMARCA study (Russian acronym: R ussian InvE stigation of M ethotrexA te and biologics in eaR ly aC tive inflammatory A rthritis) included patients with early and established active RA, not treated previously with subcutaneous methotrexate (SC MT) injections and biologics. Totally 264 pts were included, 161 out of them (29 males, 132 females, 50, 3% with disease duration <6 mo., 84% RF(+), 82% anti-CCP(+), DAS28 5, 47±1, 14, SDAI 30, 2±14, 3) were followed up for at least 12 mo. All patients received SC MT as a fist-line therapy, starting from 10 mg/week with fast dose escalation up to 25-30 mg/week. Use of steroids was limited to continuation of previously administered low oral doses (in 15% pts) and intra-articular injections (2 doses per 3 mo). Therapy revision and initiation of biologics in combination with SC MT (adalimumab, certolizumab, or abatacept), was made every 3 mo (or more often if indicated) in order to reach T2T targets. Results: The T2T targets by Month 12 were achieved in 120 (74, 5%) pts, including LDA (3, 3<SDAI<11) in 36, 6%, and remission (SDAI<3, 3) in 37, 9% pts. Need in combination with biologics was obvious in 97 (60, 2%) pts (in pts with RA duration <6 mo. – in 52%, p <0, 05), biologics were administered 4, 2±3, 5 mo. after initiation of SC MT. The following parameters were significantly different (p<0, 05) between the groups on SC MT monotherapy (MT-mono) and on combination (MT+BIO) therapy: disease duration, baseline (Bl) values of TJC28, HAQ, SDAI, CRP (mg/l), changes (Δ) in DAS28, SDAI, CDAI scores and CRP level after first 12 weeks of therapy. Linear regression analysis of these variables to predict the need in MT+BIO showed, that the most important parameters were: BlSDAI, BlHAQ, BlCRP, and ΔDAS28, ΔSDAI, and ΔCDAI scores after first 12 weeks of therapy. ROC-analysis yielded the following AUC values: BlCRP – 0, 353 ( p =0, 011), BlSDAI – 0, 376 ( p =0, 031), BlHAQ – 0, 403 ( p =0, 092), ΔDAS28 – 0, 746 ( p <0, 001), ΔSDAI – 0, 668 ( p =0, 003), ΔCDAI – 0, 686 ( p =0, 001). Therefore, disease activity scales showed the strongest predictive power, preferable cut off-points for prediction of the necessity in MT+BIO were: ΔDAS28 ≤1, 3, ΔSDAI ≤14, ΔCDAI ≤11. Conclusions: Dynamics in DAS28, SDAI and CDAI disease activity scores in 12 weeks after initiation of SC MT allow to predict the necessity of combination with biologics within 12 months in the treatment regimen in accordance to T2T strategy. Disclosure of Interest: None declared